Dispersal capacity of Monochamus galloprovincialis, the European vector of the pine wood nematode, on flight mills. (19th December 2013) - David, G.; Giffard, B.; Piou, D.; Jactel, H.
Abstract The pine wood nematode (Bursaphelenchus xylophilus), which causes the symptoms of pine wilt disease, is recognized worldwide as a major forest pest. It was introduced into Portugal in 1999. It is transmitted between trees almost exclusively by longhorn beetles of the genus Monochamus, including, in particular, M. galloprovincialis (Coleoptera: Cerambycidae) in maritime pine forests. Accurate estimates of the flight capacity of this insect vector are required if we are to understand and predict the spread of pine wilt disease in Europe. Using computer‐linked flight mills, we evaluated the distance flown, the flight probability and speed of M. galloprovincialis throughout adulthood and investigated the effects of age, sex and body weight on these flight performances, which are proxies for dispersal capacity. The within‐population variability of flight performance in M. galloprovincialis was high, with a mean distance of 16 km flown over the lifetime of the beetle. Age and body weight had a significant positive effect on flight capacity, but there was no difference in performance between males and females. These findings have important implications for managing the spread of the pine wood nematode in European forests.